2015
DOI: 10.3892/etm.2015.2545
|View full text |Cite
|
Sign up to set email alerts
|

Effect of catheter ablation versus antiarrhythmic drugs on atrial fibrillation: A meta-analysis of randomized controlled trials

Abstract: Abstract. The aim of the present study was to compare the health outcomes of catheter ablation therapy against those of antiarrhythmic drugs (AADs) in the management of atrial fibrillation (AF). The effects of catheter ablation and AADs on a number of parameters were compared, including AF recurrence, all-cause mortality, stroke/transient ischemic attack (TIA) and quality of life (QoL). A systematic literature search of PubMed, Embase and the Cochrane Central Register of Controlled Trials was conducted to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 32 publications
0
28
0
7
Order By: Relevance
“…Selection of appropriate patients is a complex process that requires careful consideration of clinical factors including symptoms, presence of heart disease, obesity, sleep apnoea, left atrial size, duration of persistent AF, and patient preferences 44 . A few large administrative registries have reported that, after multivariable adjustments, women are less likely to undergo catheter ablation than men 34,45 , and that women are underrepresented in catheter ablation meta-analyses 4649 . A review on the association between sex and outcomes of catheter ablation for AF has also reported that women are referred less often and later than men 50 .…”
Section: Rate and Rhythm Controlmentioning
confidence: 99%
“…Selection of appropriate patients is a complex process that requires careful consideration of clinical factors including symptoms, presence of heart disease, obesity, sleep apnoea, left atrial size, duration of persistent AF, and patient preferences 44 . A few large administrative registries have reported that, after multivariable adjustments, women are less likely to undergo catheter ablation than men 34,45 , and that women are underrepresented in catheter ablation meta-analyses 4649 . A review on the association between sex and outcomes of catheter ablation for AF has also reported that women are referred less often and later than men 50 .…”
Section: Rate and Rhythm Controlmentioning
confidence: 99%
“…Given that CA is an established treatment for AF with efficacy consistently superior to medical therapy, 36,37 an overview of the procedure is warranted. The cornerstone of the AF ablation is electrical isolation of the PVs by the targeted deployment of radiofrequency (essentially heat energy) ablation (RFA) lesions around the PV Ostia; CA is performed percutaneously via endovascular catheters.…”
Section: Pv Isolation (Pvi)/af Ablationmentioning
confidence: 99%
“…Differences in ablation success rates reported in clinical trials are attributable to variables such as AF classification, concomitant risk factors and the definition of success . The AADs most often used in these trials include amiodarone, sotalol, dofetilide and flecainide.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…The AADs most often used in these trials include amiodarone, sotalol, dofetilide and flecainide. Suppressive antiarrhythmic drugs were commonly used for the first 1‐3 months post‐ablation and the majority of the trials followed patients for 1‐year post‐procedure . It is common for AF to preclude recurrences occurring in the 3‐month “blanking” period following the procedure due to high rates of early recurrences that may not correlate with long‐term clinical success .…”
Section: What Is Known and Objectivementioning
confidence: 99%